(x² + 2x)(x² + 2x - 2) = 3
Сделаем замену :
x² + 2x = m , тогда x² + 2x - 2 = m - 2
m(m - 2) = 3
m² - 2m - 3 = 0
По теореме Виета :
m₁ = - 1
m₂ = 3
1) x² + 2x = - 1
x² + 2x + 1 = 0
(x + 1)² = 0
x + 1 = 0
x₁ = - 1
2) x² + 2x = 3
x² + 2x - 3 = 0
x₂ = - 3
x₃ = 1
ответ : - 3 ; - 1 ; 1
(x² + 2x)(x² + 2x - 2) = 3
Сделаем замену :
x² + 2x = m , тогда x² + 2x - 2 = m - 2
m(m - 2) = 3
m² - 2m - 3 = 0
По теореме Виета :
m₁ = - 1
m₂ = 3
1) x² + 2x = - 1
x² + 2x + 1 = 0
(x + 1)² = 0
x + 1 = 0
x₁ = - 1
2) x² + 2x = 3
x² + 2x - 3 = 0
x₂ = - 3
x₃ = 1
ответ : - 3 ; - 1 ; 1